LETROZOLE COMPARED WITH CLOMPIHENE CITRATE FOR POLYCYSTIC OVARIAN SYNDROME : A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
According to the Consensus on the Management of PCOS, polycystic ovary syndrome, is an endocrine condition that produces oligo-anovulation, clinical and biochemical symptoms of hyperandrogenism, and distinctive ovarian morphological characteristics on ultrasonographic examination. PCOS is also associated with a higher risk of endometrial cancer. Both hyperandrogenism and anovulation are difficult conditions to manage. PCOS women often have higher GnRH pulsatility, which in turn causes increased pituitary LH secretion and an elevated LH/FSH ratio. Granulosa cells are responsible for the conversion of androgens to estrogen and the maturation of follicles, while LH is responsible for promoting androgen synthesis in theca cells. Intraovarian androgens produce atresia in later antral stages, although they do boost initial follicle recruitment by increasing preantral and early antral follicle growth. In contrast to CC on its own, letrozole was shown to increase the number of live births, and the overall level of evidence was moderate. There was insufficient evidence that there was a difference in the rate of live births between CC plus metformin and CC alone, and the overall certainty of the evidence was poor due to the risk of bias and imprecision. When contrasted with the use of CC by itself, the potential benefit of CC in combination with metformin was more apparent in women whose baseline blood insulin or HOMA-IR values were higher than average. In comparison to clomiphene citrate, letrozole was related with higher rates of ovulation, pregnancy, and successful delivery of a live baby. Despite the fact that the quality of the data is inconsistent, one study recommends letrozole over clomiphene citrate as an ovulation induction medicine for women who have infertility and PCOS.